Предмет: Алгебра,
автор: denisgavrilcenko0
Знайдіть значення виразу (x-4)^2+2(4+x) (4-x)+(x+4)^2 при х=1,2
А)64
Б)32
В)48
Г)72
Ответы
Автор ответа:
1
- Ответ:
Объяснение:
(х-4) ²+2 (4+х) (4-х) + (х+4) ²=
= (х²-2*4*х+4²) + 2 * (4²-х²) + (х²+2*4*х + 4²) =
= х²-8 х+16+2*16-2 х²+х²+8 х+16=
= (х²-2 х²+х²) + (-8 х+8 х) + (16+32+16) =
=64
Проверим: при х = (-1,2)
((-1,2) - 4) ²+2 (4 + (-1,2)) (4 - (-1,2)) + (-1,2+4) ²=
= (-5,2) ² + 2 * (2,8) * (5,2) + (2,8) ²=
= 27,04+29,12+7,84=64
Похожие вопросы
Предмет: Физика,
автор: humpme
Предмет: Українська мова,
автор: 19282722992
Предмет: Математика,
автор: anegichsaaa
Предмет: Информатика,
автор: UnderScq
Предмет: Математика,
автор: ikot53611